Application of preoperative registration and automatic tracking technique for image-guided maxillofacial surgery. Issue 1 (1st January 2016) - Zhang, Wenbin; Wang, Xudong; Zhang, Jianfei; Shen, Guofang
Abstract: Objective: To investigate the practicality of preoperative registration technique in navigational surgery of facial skeleton. Methods: Five cases were underwent navigational surgery with the preoperative registration technique. The accuracy of registration process was determined, and the deviation between planning model and postoperative computed tomography (CT) model was detected. Results: In each case, the preoperative registration was successful for navigational surgery. Preoperative registration and automatic tracking enabled registration free in the operation procedure. The registration precision measured by the system was less than 0.8 mm. The deviation between the intraoperative anatomy and the CT image was less than 1.5 mm. Conclusions: Preoperative registration technique demonstrates the potential for improved workflow and accuracy in navigational surgery procedures. This technique was found to be particularly advantageous in cases of mandible navigational surgery in which the dynamic reference frame's hard to be fixed.